"The Beautiful is the Symbol of the Morally Good": Judgments of Beauty and the Supersensible in Kant's Critique of Aesthetic Judgment - Fisher, Naomi (Proceedings of the American Catholic Philosophical Association, 2020)
In the Critique of the Power of Judgment, Kant claims that "the beautiful is the symbol of the morally good." In this article I offer an interpretation of this claim. According to Kant's conception of a symbol, the form of judgment operative in judgments of beauty can also be applied to morality. This parallel application highlights that we are directed at an end which cannot be determined by theoretical cognition. I argue that beauty's symbolism of morality depends upon the solution to the Antinomy of Taste, and Kant's conclusion that judgments of taste are grounded in the concept of the supersensible. Such an interpretation renders intelligible Kant's remark that judgment makes possible a transition from nature to morality. Namely, beauty demonstrates to us nature's openness to transcendence, and thus is a symbol, a making-sensible of our own transcendence and practical determination of nature.